Rhetorical Structure of Students’ Speech in Public Speaking Class - Akbar, Muhamad Kenzo; Syafryadin, Syafryadin; Sujarwati, Iis; Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2024)
Speech is part of the communication process, and this communication is effective if the message delivered by the speaker can be received precisely as it exists in the speaker's mind. This study aims to identify the move and step’s rhetorical elements, commonly taught in public speaking courses. This study's research design was qualitative design. 20 speeches from English education students in the University of Bengkulu public speaking course served as the research object. Using an adapted model. In this study, researchers used the checklist method as a research instrument. The frequency and steps of agreement in this study were determined manually. This study was analyzed by tabulating frequency data and providing examples of the moves and steps seen in the video. It was found that 2 moves had a frequency of 100% and 3 steps of 12 steps analyzed had a frequency of 100%. The moves are Introduction and Content. Steps with a frequency of 100% are Greeting the audience, Hortatory/narration, and presenting an argument. Meanwhile, 3 steps with a 90% - 95% frequency are announcing the topic, suggestion, and thanking. There are 2 steps that never appear in this study: outlining structure/indicating scope and describing a process/series of events. In this study, the researchers concluded that 2 moves and 3 steps were found with a frequency percentage of 100%, and 3 steps were found with a frequency percentage of 90% - 95%. In addition, 2 steps never appeared in this study